George Washington Paschal, A Digest of the Laws of Texas: Containing Laws in Force, and the Repealed Laws on Which Rights Rest, at 1322-24, An Act to Regulate the Keeping and Bearing of Deadly Weapons, Art. 6512. (Vol. 2, 1873) - (:unkn) unknown (General Publisher, 1871)
Any person carrying on or about his person, saddle, or in his saddle-bags, any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass-knuckles, bowie-knife, or any other kind of knife manufactured or sold for the purpose of offense or defense, unless be has reasonable grounds for fearing an unlawful attack on his person, and that such ground of attack shall be immediate and pressing; or unless having or carrying the same on or about his person for the lawful defense the state, as a militiaman in actual service, or as a peace officer or policeman, shall be guilty of a misdemeanor
--
Keywords: CARRY